THE CONTRIBUTION OF ZAKAT, INFAQ, AND SADAQAH (ZIS) DIGITALIZATION BY BAZNAS BANDAR LAMPUNG CITY IN ADVANCING THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Hadi Yanto; Heni Noviarita; Erike Anggraeni (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study analyzes the role of digitalization in the management of Zakat, Infaq, and Shadaqah (ZIS) by BAZNAS Bandar Lampung City in supporting the Sustainable Development Goals (SDGs), particularly SDG 1 (poverty eradication). The research employs a qualitative descriptive method, with data collected through in-depth interviews with ZIS beneficiaries (mustahik), triangulation with BAZNAS officials, direct observation, and document analysis including annual reports and infographics. Findings reveal that digitalization has enhanced the efficiency, transparency, and accountability of zakat fund collection through digital platforms such as QRIS, bank transfers, and the SIMBA application for internal reporting. However, digital services for mustahik especially in proposal submissions, impact tracking, and distribution monitoring remain underdeveloped. ZIS programs have contributed positively to poverty alleviation, particularly through consumptive assistance and education-based scholarships. Evaluation using the National Zakat Index (IZN) 2.0 indicates that governance and collection aspects are effective, while areas concerning impact and technological utilization require further improvement. Overall, digitalization has played a significant role in aligning ZIS management with SDG targets. Nonetheless, optimizing digital access for mustahik and strengthening empowerment-based programs are crucial steps to maximize the impact of zakat distribution in advancing sustainable development at the local level